STRUCTURAL MODEL OF THE ROLE OF HYDROPONIC VEGETABLE AGRIBUSINESS INSTITUTIONS TOWARDS FOOD SELF RELIANCE IN BORDER AREAS - Rayhana Jafar; Nurlela M; Meli Sarah (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
The role of institutions is crucial in the hydroponic vegetable agribusiness subsystem, encompassing input procurement to marketing to enhance product quality and value. However, the institutions in the hydroponic vegetable agribusiness system in Tarakan City have not shown a significant role, indicating the non-functional institutionalization of related institutions. This has led to both horizontal and vertical sectoral egos and conflicts between institutions. This research uses a systems approach to identify and study the institutions involved and the structural model of the hydroponic vegetable agribusiness institution. The research method used was descriptive qualitative with Interpretative Structural Modeling (ISM) data analysis techniques. Purposive sampling was utilized for data collection. The findings reveal that institutions that should have a role in hydroponic vegetable agribusiness are the Food Security and Agriculture Department, Agricultural Extension, Middlemen, Cooperative Department, Small and Medium-sized Enterprises (SMEs), Industry and commerce Department, Cooperatives, Banks, Association of Farmers Groups, Farmer Group, Agricultural Shops, and Central of Bureau of Statistics. The institutions' roles include policy-making, facilitation, provision of farming inputs and infrastructure, financial services, lending, selling, marketing, and processing of products. The structural model of the institution's involvement in hydroponic vegetable agribusiness in Tarakan City consists of four levels, with the Key Actor Institution at Level 1, including the Food Security and Agriculture department, Agricultural Extension, Middlemen, Farmer Groups, and Agricultural Shops. The fifth institution is expected to be a driving force in hydroponic vegetable agribusiness.Keywords: Hydroponics, Structural Model, Role of Institutions